Food, culture, and human health in Alaska: an integrative health approach to food security - Loring, Philip A.; Gerlach, S.C. (Environmental science & policy, 2009)
Multiple climatic and socioeconomic drivers have come in recent years to interfere with the ability of Alaska's ‘bush’ communities to achieve food security with locally available food resources. Livelihoods traditionally centered on the harvest of wild, country foods, are transitioning to a cash economy, with increasing reliance on industrially produced, store-bought foods. While commercially available foods provide one measure of food security, availability and quality of these foods is subject to the vagaries and vulnerabilities of a global food system: access is dependent on one's ability to pay; most importantly, perhaps these foods often do not fulfill many of the roles that country foods have played in these communities and cultures. This transition is having severe consequences for the health of people and viability of rural communities, yet in ways not always tracked by conventional food security methodologies and frameworks. This paper expands the discussion of food security, premised on an integrative model of health that links sociocultural, ecological, psychological, and biomedical aspects of individual and community health. We use the Alaska case to illustrate that if food security is to be understood as a matter of human health, then our definitions of and designs for food security must recognize food's multifaceted and often regionally nuanced role in creating positive health outcomes.